Performance of the Johannesburg Stock Exchange as a growth catalyst of small medium enterprises - Maluleka, Julia (My University, 2023)
Small and medium-sized enterprises (SMEs) seek equity financing through stock exchanges to fund future growth opportunities, acquisitions, existing projects, and investment opportunities. The Johannesburg Stock Exchange (JSE) and Alternative exchange (AltX) provide a platform for SMEs to list and raise capital. In this paper, we investigate the impact that the AltX and JSE has on the growth, operating performance, and market performance of listed SMEs. The panel regression model is used to investigate this relationship. We used revenue growth as a proxy for growth, earnings per share (EPS) as a proxy for operating performance and share price as a proxy for market performance. Our independent variables were small businesses characteristics (age, size, leverage, dual listing, and industry) and stock market indicators (market liquidity, stock market capitalisation, volume, capital raised, and IPO ratio). GDP growth was included as a control variable. The panel data used in this study were collected from 2007 to 2020, and the estimation sample consists of 34 companies listed on AltX and 49 companies listed on the JSE mainboard. The empirical findings show that leverage, market liquidity and the industrials industry have an impact on the revenue growth of listed SMEs. The results of the impact of listing on the operating performance of listed small businesses using EPS as a proxy show that company age, size, dual listing, capital raised, and industries such as industrials, technology, consumer services, and healthcare influence the EPS of small businesses listed on the JSE and AltX. Our findings on SMEs market performance indicate that company size, age, leverage, dual listing, IPO ratio and industries such as consumer services, financials, industrials, technology, and telecommunications all have a significant impact on the share price of listed SMEs. We also found that the JSE and AltX have a differential impact on listed small businesses.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Finance and Investment to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2022
Keywords: Small and medium-sized enterprises (SMEs); Stock exchange; Investment